Colloidal Suspension Properties of Carbonaceous Nanomaterials Enhanced by Using Li as Dopant - Zhu, Lei; Meng, Ze-Da; Chen, Ming-Liang; Choi, Jong-Geun; Park, Chong-Yeon; Lee, Shi-Choon; Hong, Dae-Seung; Oh, Won-Chun (Asian Journal of Chemistry, 2011)
A colloidal suspension of carbonaceous nanomaterials for heat exchangers has attracted increasing research attention. In this study, a simple route used to synthesize lithium treated carbonaceous nanomaterials was studied. The dispersion effect, electrical conductivity, thermophysical properties of the Li-carbon-nanocolloids system were introduced and discussed. The results show that these properties were largely enhanced, which could be due to not only the outstanding physical and electrical properties of the carbon nanomaterials but also to the introduction of lithium ions.